2018
DOI: 10.5125/jkaoms.2018.44.2.66
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic melanoma of the oral cavity: diagnostic pitfalls and clinical characteristics

Abstract: ObjectivesDesmoplastic melanoma of the oral cavity is an extremely rare condition that is often confused on initial diagnosis with non-melanotic benign lesion or spindle cell tumors. The purpose of this article was to raise awareness of the disease using a literature review.Materials and MethodsWe analyzed 19 desmoplastic melanoma cases reported in the literature and added our experience. Data on clinical, histopathology, treatment, and survival were retrieved and analyzed. Survival analysis was by the Kaplan-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…HMB45 staining was not observed with any of the desmoplastic variants while only one out of five was stained with Melan A [1]. A similar finding was observed by Seung Ki Min who treated 12 oral melanoma tissue samples with S100 and HMB45 and found that S100 was positive with all 12 cases while HMB45 failed to stain 7 out of 12 cases [8]. The role of S100 in the diagnosis of this rare variant is extremely encouraging where HMB45 fails [9].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…HMB45 staining was not observed with any of the desmoplastic variants while only one out of five was stained with Melan A [1]. A similar finding was observed by Seung Ki Min who treated 12 oral melanoma tissue samples with S100 and HMB45 and found that S100 was positive with all 12 cases while HMB45 failed to stain 7 out of 12 cases [8]. The role of S100 in the diagnosis of this rare variant is extremely encouraging where HMB45 fails [9].…”
Section: Discussionmentioning
confidence: 58%
“…Although the sensitivity of this marker is low, the very fact that this antibody does not appear to react with any nonmelanocytic tissues suggests a good specificity for this marker [10]. Among the studies included in our review, a study done by Chuan-Hang Yu suggested HMB45 to be a less sensitive marker than S100 but the staining intensity of HMB45 to be higher than that of S100 and Melan A [2,[8][9][10][11][12][13]. The role of S100 in diagnosing metastatic melanomas was suggested to be more significant than that of HMB45 and Melan A [2].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…López et al reported on a bad prognosis of primary mucosal melanoma with 5-year disease-free survival rates of less than 20% [ 14 ]. With a special focus on desmoplastic melanoma of the oral cavity, poor 5-year disease-free and overall survival rates (0%, 55%) were reported [ 15 ]. A review reported recurrences in 11.6% and mortality in 54.8% of cases of primary oral melanoma [ 16 ].…”
Section: Discussionmentioning
confidence: 99%